2019
DOI: 10.1093/ecco-jcc/jjz115
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 and Mucosal CD14+ Monocyte-Like Cells Induce IL-8 in Colonic Memory CD4+ T Cells of Patients With Ulcerative Colitis but not Crohn’s Disease

Abstract: Background and Aims CD14+ mononuclear phagocytes [MNPs] and T cells infiltrate colon in ulcerative colitis [UC]. Here we investigated how CD14+ MNPs and the cytokines they produce shape the colonic effector T cell profile. Methods Colonic or mesenteric lymph node [mLNs] CD4+ T cells isolated from UC or Crohn’s disease [CD] patients were stimulated with cytokines or autologous CD14+ MNPs. Cytokine expression was assessed by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…It is now clear that the frequency and number of Mfs among intestinal LP cells is increased in IBD patients compared to controls, especially in active lesion areas (132,221,223,225,226,228,246,263,(267)(268)(269)(270)(271)(272) (Figure 5E). More specifically, the augmentation of intestinal Mfs is due to an increase in the frequency of immature Mfs among LP cells, despite that somewhat different surface markers and combinations thereof have been used to characterized them (i.e., HLA-DR or CD11c levels; scRNA-seq) (132,221,223,225,226,228,256,263,270,(272)(273)(274)(275) (Figure 5F). This accumulation seems to be due to the inflammatory intestinal microenvironment of IBD patients, which boosts the recruitment of classical monocytes through mechanisms involving CCL2, IL-8, and TGF-β signaling (223,276).…”
Section: Phenotype and Frequency Of Intestinal Mucosa Macrophagesmentioning
confidence: 96%
See 1 more Smart Citation
“…It is now clear that the frequency and number of Mfs among intestinal LP cells is increased in IBD patients compared to controls, especially in active lesion areas (132,221,223,225,226,228,246,263,(267)(268)(269)(270)(271)(272) (Figure 5E). More specifically, the augmentation of intestinal Mfs is due to an increase in the frequency of immature Mfs among LP cells, despite that somewhat different surface markers and combinations thereof have been used to characterized them (i.e., HLA-DR or CD11c levels; scRNA-seq) (132,221,223,225,226,228,256,263,270,(272)(273)(274)(275) (Figure 5F). This accumulation seems to be due to the inflammatory intestinal microenvironment of IBD patients, which boosts the recruitment of classical monocytes through mechanisms involving CCL2, IL-8, and TGF-β signaling (223,276).…”
Section: Phenotype and Frequency Of Intestinal Mucosa Macrophagesmentioning
confidence: 96%
“…This seems to be due to immature Mf accumulation within the total Mf population in Crohn's patients. Indeed, Chapuy et al have recently shown that immature Mfs from IBD patients, but seemingly not mature Mfs, induce Th17 cells, as well pathologic IFN-y + IL-17 + T cells (303), from autologous colonic CD4 + T cells mainly through their production of IL-1β (228,272). Corroborating this, Martin et al have shown that, while initial steps of lymphocyte aggregate formation depend on DCs, immature Mfs likely participate in T cell activation in situ (263).…”
Section: Function Of Intestinal Mucosa Macrophagesmentioning
confidence: 99%
“…In CD and UC patients, both CD163 − and CD163 + MNPs produced pro-inflammatory cytokines (IL-1β, IL-6, IL-12p40, and IL-23). CD163 + MNPs expressed more TNF-α and IL-10 than CD163 − MNPs, which are the major contributors to IL-23 and IL1β [31,39]. The CD163 − , but not CD163 + , MNPs promoted Th17 and Th17/Th1 memory responses in an IL-1β-dependent manner [31,39], which have been suggested to be pathogenic in IBD [40][41][42][43].…”
Section: Mnps In Intestinal Mucosa During Inflammationmentioning
confidence: 99%
“…Stratification of colonic CD14 + MNPs according to CD64 and CD163 expression allowed the discrimination of two phenotypically, morphologically, and functionally distinct populations in IBD patients. Only CD14 + CD64 + CD163 −/dim , and more particularly CD163 − but not CD163 + cells, accumulated in inflamed mucosa of IBD patients in proportions that correlate with endoscopic disease severity in CD, regardless treatment history, demographics and disease behavior or location [31,39]. CD14 + CD64 + CD163 − MNPs displayed monocyte morphology, whereas CD163 + MNPs resembled Mφ with cytoplasmic vacuoles [31].…”
Section: Mnps In Intestinal Mucosa During Inflammationmentioning
confidence: 99%
See 1 more Smart Citation